Management zone‐based estimation of positive and negative nitrous oxide flux in organic corn fields. Issue 4 (8th June 2022) - Xia, Yushu; Wander, Michelle
Abstract: Accurate estimation of field‐scale nitrous oxide (N2 O) fluxes is hindered by their considerable variability and the fact that soils can be both sources and sinks for N2 O. This is particularly challenging for organic systems that have complex rotations and inputs. This study used digital soil mapping and survey datasets to explore spatial controls of N2 O "hot moments" induced by precipitation with strategic sampling designed to identify covariates that influence N2 O emission patterns. Soil N2 O fluxes after rain events were measured within three management zones (MZs, "High, " "Medium, " "Low") delineated by crop productivity, soil fertility, and hydrological features in eight organic fields during the 2018 and 2019 corn ( Zea mays L.) growing seasons. Hot moments typically occurring 1 d after rain events included both positive and negative N2 O fluxes. The MZ‐based design identified regions with different patterns in positive and negative flux, with hotspots for both being co‐located with areas of poorer drainage and higher soil fertility. Covariates that best explained hot moments included corn growth stage, soil moisture, slope, texture, and soil organic matter. Negative fluxes were large enough to offset positive fluxes so that averaged net N2 O fluxes were only significantly different between the "High" and "Low" MZs. Had negative fluxes been omitted, averaged N2 O fluxes would have increased estimates by 37%. Processes that lead to N2 O consumptions must be better quantified to improve the estimation of management‐associated net N2 O flux. Use of strategic sampling can efficiently capture needed information, but spatial and temporal weighting is needed to scale up results. Core Ideas: Inherent soil properties identified management zones that differ in temporal N2 O flux. Dynamic properties improved prediction of N2 O flux from organically managed fields. Strategic sampling following rain captured spatial and temporal N2 O flux patterns. Nitrous oxide hotspots occur where substrate abundance and O2 limitations are greatest. Post‐rain N2 O loss is overestimated when negative N2 O hotspots are not considered.